Is Adversity a School of Wisdom? Experimental Evidence on Cooperative Protection Against Stochastic Losses - Andreas Nicklisch; Sonja Köke; Andreas Lange (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We investigate the dynamics of voluntary cooperation to either reduce the size or the probability of stochastic losses. For variants of a repeated four person prisoner's dilemma game, we show that cooperation is larger and more stable when it affects the probability rather than the size of the adverse event. We provide crucial insights on behavioral adaptation: defecting players are more likely to switch to cooperation after experiencing an adverse event, while existing cooperation is reinforced when the losses do not occur. This behavior is consistent with simple learning dynamics based on ex post evaluations of the chosen strategy.
Keywords: Q54; H41; C92; 330